Biblia o ludziach starszych - Tronina, Antoni (Vox Patrum, 2011)
The author formulates the topic in a synthetical way, elaborating on it in three parts: Hebrew Bible, deuterocanonical books and message of the New Testament. The fake dilemma (gerontocracy or gerontophobia) is overcome in the light of Revelation: Bible presents the wisdom as a source of truth and goodness, and as a solidarity with the elderly, because only the truth can set people free (J 8, 23). The truth revealed in Christ can also overcome the modern forms of discrimination in the world.